Development of catalysts in chemical interesterification for glycerol-free biodiesel production: Critical analysis - Chok, Weng Shan (2021)
Biodiesel production is commonly carried out via transesterification in which glycerol is produced as the by-product. Glycerol has a low market value and it is normally treated as waste product from the reaction. Separation process is also required to isolate the glycerol to obtain pure biodiesel. In fact, glycerolfree biodiesel production can be achieved through chemical interesterification which is an alternative route to the conventional transesterification reaction. Instead of glycerol, triacetin is produced as the by-product from chemical interesterification. Similar to conventional transesterification, chemical interesterification requires catalyst as well. This study analysed and compared the catalyst performance reported in the literature to find the best catalysts for the reaction. Different types of catalysts such as homogeneous acid (14%), homogeneous base (38%), heterogeneous acid (24%) and heterogeneous base (24%) catalysts were obtained from a total of 55 catalysts reported in 30 journals from year 2011 to 2020. Different aspects were analysed such as the biodiesel yields, reaction temperature, reaction time, catalyst amount and acyl acceptor to oil molar ratio. CH3NaO (base) and CaO (base) were selected as the best homogeneous catalyst and heterogeneous catalyst, respectively based on their overall aspects. Based on the results reported, CH3NaO was able to achieve 93% biodiesel yield with 20:1 methyl acetate to oil molar ratio (MAOMR) and 0.05:1 catalyst to oil molar ratio (COMR) at 60 ℃ for 0.2 hour (12 minutes). On the other hand, CaO was able to generate 90.5 wt.% of biodiesel with 30:1 ethyl acetate to oil molar ratio (EAOMR) and 4.0 wt.% catalyst at 80 ℃ for 5 hours. Potential catalysts to be used in chemical interesterification were also suggested such as tungsten phosphoric acid and sodium silicate. These are heterogeneous acid and base catalysts that were reported in transesterification with good performances. This analysis ultimately enables more efficient production of biodiesel through interesterification process in the future by selecting the suitable catalysts. This study also provides a direction for future catalyst development in chemical interesterification for biodiesel production.